(untitled) (Nigerian Journal of Technology, 2017)
This paper presented the results of the shear strength parameters and compaction characteristics of lateritic soil stabilized with a combination of Lime and Coconut husk ash (CHA) in various percentages using two compaction methods namely; British standard heavy (BSH) and British standard light(BSL). Undrained triaxial test was conducted to determine shear strength parameters of the stabilized soil with confining pressures of 69kN/m2, 138kN/m2 and 276kN/m2, after preliminary tests had been carried out to determine index properties of the soil. The test was conducted on a mixture of natural soil with 4%lime, which gave least plasticity index and percentages of CHA from 0-12% by dry weight of soil. The BSL and BSH were applied on mixture of soil + 4% lime + percentages of CHA ranging from 4-20% by dry weight of soil. The most plausible improvement in maximum dry density was obtained by adding 4% lime + 12% CHA and 4% lime + 16% CHA using BSH and BSL respectively. The results also show significant improvement in angle of internal friction and cohesion of the soil at 6% and 8%CHA addition respectively. http://dx.doi.org/10.4314/njt.v36i4.4